Circulating Autoantibodies to Endothelial Progenitor Cells: Binding Characteristics and Association with Risk Factors for Atherosclerosis - George, Jacob; Matucci-Cerinic, Marco; Bar, Iris; Shimoni, Sara (PloS one, 2014)
Endothelial progenitor cells (EPC) are committed to transform into EC promoting vasculogenic ischemic repair. Anti-endothelial cells (AECA) have been described in various disorders with an associated vascular damage. Herein, we explored a novel circulating population of IgG reactive with EPC, in patients with differential risk profile for atherosclerotic vascular disease. A novel cyto-ELISA system was established where the coated cells were late outgrowth EPC. Levels of anti-EPC antibodies were determined in 100 subjects and differential risk score for atherosclerosis, as well as to circulating EPC levels and the inflammatory markers IL-6 and C-reactive protein. To study endothelial cell (EC) activating properties, sera were tested for their ability to induce VCAM-1 expression in a cell ELISA system. Detectable levels of anti-EPC antibodies, that correlated with age, Framingham risk score and CRP concentrations but did not associate with levels of LDL, HDL, hypertension or diabetes, were detected. Anti-EPC antibodies were distinct from EC binding antibodies as shown by competitive inhibition studies, and have been positively correlated with the extent of EC activation manifested by in vitro VCAM-1 expression. This is the first study showing a newly defined subgroup of self-antibodies binding EPC and associating positively with the Framingham risk score. Further studies are required to characterize and test this interesting subset of EPC binding autoantibodies and their potential significance.